Global Metabolomics Reveals That Vibrio natriegens Enhances the Growth and Paramylon Synthesis of Euglena gracilis - Ouyang, Ying; Chen, Shuyu; Zhao, Liqing; Song, Yiting; Lei, Anping; He, Jiayi; Wang, Jiangxin (Frontiers in Bioengineering and Biotechnology, 2021)
The microalga Euglena gracilis is utilized in the food, medicinal and supplement industries. However, its mass production is currently limited by its low production efficiency and high risk of microbial contamination. In this study, physiological and biochemical parameters of E. gracilis co-cultivated with the bacteria Vibrio natriegens were investigated. A previous report the benefits of E. gracilis and V. natriegens co-cultivation, however, no bacterium growth and molecular mechanisms were further investigated. Our results show that this co-cultivation positively increased total chlorophyll, microalgal growth, dry weight and storage sugar paramylon content of E. gracilis compared to the pure culture without V. natriegens. This analysis represents the first comprehensive metabolomic study of microalgae-bacterial co-cultivation, with 339 metabolites were identified. This co-cultivation system was shown to have synergistic metabolic interactions between microalgal and bacterial cells, with a significant increase in methyl carbamate, ectoine, choline, methyl N−methylanthranilate, gentiatibetine, 4R−aminopentanoic acid and glu−val compared to cultivation of E. gracilis alone. Taken together, these results fill significant gaps in the current understanding of microalgae-bacteria co-cultivation systems and provide novel insights into potential improvements for mass production and industrial applications of E. gracilis.